Licenciandas em pedagogia na Rede de Aprendizagem da Docência (ReAD): compreensões sobre a docência - Marini, Carolina (2018)
The objective of the this dissertation is to investigate what is the comprehension Pedagogy students have on subjects related to teaching and its characteristics: professionalism and the process of teaching professionalization, teacher training and teacher education, teacher’s professional identity, teachers’ continuing professional development. The data that were analyzed consist of narratives written by graduate students, produced in the context of a blended learning (on-line) environment, the “Rede de Aprendizagem e Desenvolvimento da Docência” (ReAD). The ReAD promotes intergerational partnership (interactions between Primary School teachers – both experienced and beginner teachers – and Pedagogy/Education undergraduate students), based on a blended learning perspective (combining aspects of face-to-face synchronous interactions with on-line asynchronous interactions), working as a hybrid space where the gap between educational sciences/theory and teacher’s practice/knowledge is reduced. The data shows that ReAD actually worked as a learning environment, because its participants were able to exchange information, experience and knowledge in the course of on-line interactions (intergerational partnership). It also shows that ReAD helped the students build their professional identity as future teachers, since they were able to think about teachers’ practice through different themes and perspectives. For that reason, the students were able to make projections about what kind of teacher they would like to be and/or what kind of teachers’ practice they would like to put into practice when they become teachers. When they were able to talk about teacher training, they described what kind of education they were been receiving and what kind of education they believe that should be offered to Pedagogy/Education undergraduate students. Their thoughts on teachers’ professional development are: they believe it happens as a continuing process, so learning (how) to be a teacher is something that doesn’t happen only during higher education (Brazilian licentiate degree), because teachers are able to learn more about their practice as they become more experienced. The students were also able to reveal their thoughts about what a teacher is (or should be), what it takes to be a teacher.